Implementasi Cyber Counseling Dalam Meningkatkan Social Intelligence Mahasiswa Introvert Di Universitas PGRI Banyuwangi - Siti Napisah; Raup Padillah (LPPM Universitas Jambi, 2021)
Social intelligence is one's ability make sensitive to other people's feelings. Interactions between people who are not based on good social intelligence will lead to various conflicts. This situation will become an obstacle for develop quality of each student involved. Based on observations and observations made by researchers while giving courses at PGRI Banyuwangi University, in almost every class there are students who included in the introvert category. One effort can be done to help students like this is to do cyber counseling. This study aims to measure extent of implementation of cyber counseling in improving social intelligence of introverted students at PGRI Banyuwangi University. This research is an action research counseling (action research in counseling) study that designed in two cycles and each cycle performed 4 times. The overall implementation of cyber counseling with 8 times, 4 times on the elbow 1 and 4 times in cycle 2. Stages of implementation in this study include: (a) Planning, (b) Implementation, (c) Observation, and (d) Reflection. Overall results from cycle 1 and cycle 2, there was an increase in each social intelligence indicator that observed in 20 introverted students at the PGRI Banyuwangi University. The highest increase was in the aspects of Clarity, and Empathy, each at 50%. Based on the results of research that researchers have done, cyber counseling can used to help introverted students who tend to experience social problems. This shown in the results of observations and measurements in the process of cycle 1 and cycle 2.